Characteristic analysis of adverse reactions of five anti-TNFɑ agents: a descriptive analysis from WHO-VigiAccess - Li, Mingming; You, Ruxu; Su, Yuyong; Zhou, Hongbo; Gong, Shiwei (Frontiers in Pharmacology, 2023)
Introduction: Tumor Necrosis Factor (TNF) inhibitors (adalimumab, infliximab, etanercept, golimumab, certolizumab pegol), have revolutionized the treatment of severe immune-mediated inflammatory diseases, including rheumatoid arthritis(RA), Crohn's disease (CD), psoriatic arthritis (PSA), ankylosing spondylitis (AS) and ulcerative colitis (UC). The study assessed adverse drug reactions (ADRs) after the use of TNFα inhibitors in VigiAccess of World Health Organization (WHO) and compared the adverse reaction characteristics of five inhibitors to select the drug with the least risk for individualized patient use.The study was a retrospective descriptive analysis method in design. We sorted out 5 marketed anti-TNFα drugs and their ADR reports were gotten by WHO-VigiAccess. Data collection included data on the age groups, sex, and regions of patients worldwide covered by ADR reports, as well as data on disease systems and symptoms caused by ADRs recorded in annual ADR reports and reports received by WHO. By calculating the proportion of adverse reactions reported for each drug, we compared the similarities and differences in adverse reactions for the five drugs.Overall, 1,403,273 adverse events (AEs) related to the 5 anti-TNFα agents had been reported in VigiAccess at the time of the search. The results show that the 10 most commonly reported AE manifestations were rash, arthralgia, rheumatoid arthritis, headache, pneumonia, psoriasis, nausea, diarrhoea, pruritus and dyspnoea. The top five commonly reported AE types of anti-TNFα drugs were as follows: infections and infestations (184,909, 23.0%), musculoskeletal and connective tissue disorders (704,657, 28.6%), gastrointestinal disorders (122,373, 15.3%), skin and subcutaneous tissue disorders (108,259, 13.5%), nervous system disorders (88,498, 11.0%). The preferred terms of myelosuppression and acromegaly were obvious in golimumab.Infliximab showed significantly higher ADR report ratio in the infusion related reaction than other 4 inhibitors. The rate of ADR reports for lower respiratory tract infection and other infections was the highest for golimumab.No causal associations could be established between the TNFα inhibitors and the ADRs. Current comparative observational studies of these inhibitors revealed common and specific adverse reactions in the ADR reports of WHO received for these drugs. Clinicians should improve the rational use of these high-priced drugs according to the characteristics of ADRs.